Reborn from ashes: a new species of Tunaima (Hemiptera: Auchenorrhyncha: Cercopidae) from Southeastern Brazil - Meneghetti, Jéssica; Paladini, Andressa (Zootaxa, 2022)
A new species of Tunaima Fennah, 1968 is described and illustrated from Southeastern Brazil (Minas Gerais and Rio de Janeiro states) and a distribution map is provided. Tunaima mejdalanii sp. nov. is characterized by having tegmen brownish with two orange spots, spine-like process located between middle and apical third of dorsal margin of subgenital plate, paramere booth-shaped, dorsal margin irregular with a mountain-shape elevation. The type series of the new species belongs to the Museu Nacional (Universidade Federal do Rio de Janeiro) collection. Fortunately, this series has been sent on loan to the second author before the tragic fire that destroyed the Quinta da Boa Vista Palace in 2018.